1989
DOI: 10.1111/j.1768-322x.1989.tb00787.x
|View full text |Cite
|
Sign up to set email alerts
|

Internalization of atrial natriuretic peptide by adrenal glomerulosa cells

Abstract: Internalization of 125I-labelled atrial natriuretic peptide ([ 125I]ANP) by rat adrenal glomerulosa cells in vivo was investigated by means of an ultrastructural autoradiographic approach. One to 30 min after IV injection of [125I]ANP, silver grains were found, at the light microscope level, over all glomerulosa cells; coinjection of 20 micrograms of unlabelled ANP inhibited this binding by 64%. At the electron microscope level, the time-course study indicated maximal silver grain densities in plasma membranes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…ANP is an intracrine signaling molecule, and adrenal cortical cells are among the target cells that have been shown to internalize it. High-affinity binding sites for ANP have been identified on adrenal mitochondrial membranes, and intracellular ANP has been found in association with mitochondria (18,30,31). Interestingly, the published data are very sparse as to the regulation of mitochondria function by NPs in the kidney.…”
Section: The Np-mitochondria Signaling Axis In Physiology and Pathophysiologymentioning
confidence: 99%
“…ANP is an intracrine signaling molecule, and adrenal cortical cells are among the target cells that have been shown to internalize it. High-affinity binding sites for ANP have been identified on adrenal mitochondrial membranes, and intracellular ANP has been found in association with mitochondria (18,30,31). Interestingly, the published data are very sparse as to the regulation of mitochondria function by NPs in the kidney.…”
Section: The Np-mitochondria Signaling Axis In Physiology and Pathophysiologymentioning
confidence: 99%
“…Indeed, ANP was shown to bind directly to the mitochondrial membrane in rat adrenocortical cells. 51 , 52 It is not known whether mitochondrial membranes in adrenocortical cells or E11.5 ventricular cells harbor NPRA like binding sites and whether A7 can also bind to such sites. Differential binding of ANP vs. A7 at such intracellular vs. extracellular target sites may explain the unexpected results observed with ANP+A7 co-treatments in this study.…”
Section: Discussionmentioning
confidence: 99%
“…ANP is also an intracrine, and adrenal cortical cells are among those target cells that have been shown to internalize it. High-affinity binding sites for ANP have been identified on adrenal mitochondrial membranes, and intracellular ANP has been found in association with mitochondria (25,36,37). Other studies have shown that the direct application of recombinant ANP to renal mitochondria inhibited step 3 mitochondrial respiration and decreased the ADP-to-oxygen ratio; low molecular weight ANP also induced marked mitochondrial swelling (29).…”
Section: Atrial Natriuretic Peptidementioning
confidence: 96%